Whole-Genome Resequencing Reveals Loci Associated With Thoracic Vertebrae Number in Sheep - Li, Cunyuan; Li, Ming; Li, Xiaoyue; Ni, Wei; Xu, Yueren; Yao, Rui; Wei, Bin; Zhang, Mengdan; Li, Huixiang; Zhao, Yue; Liu, Li; Ullah, Yaseen; et al. (Frontiers in Genetics, 2019)
The number of vertebrae, especially thoracic vertebrae, is an important economic trait that may influence carcass length and meat production in animals. However, the genetic basis of vertebrae number in sheep is still poorly understood. To detect the candidate genes, 400 increased number of thoracic vertebrae (T14L6) and 200 normal (T13L6) Kazakh sheep were collected. We generated and sequenced 60 pools of genomic DNA (each pool prepared by mixing genomic DNA from 10 sheep with the same thoracic traits), with an average depth-of-coverage of 25.65×. We identified a total of 42,075,402 SNPs and 11 putatively selected genomic regions, including the VRTN gene and the HoxA gene family that regulate vertebral development. The most prominent areas of selective elimination were located in a region of chromosome 7, including VRTN, which regulates spinal development and morphology. Further investigation indicated that the expression level of the VRTN gene during foetal development was significantly higher in sheep with more thoracic vertebrae than in those with a normal number of thoracic vertebrae. A genome-wide comparison between sheep with increased and normal numbers of thoracic vertebrae showed that the VRTN gene is the major selection locus for the number of thoracic vertebrae in sheep and has the potential to be utilized in sheep breeding in the future.